Program Integrasi Ekonomi Hijau dan Ekonomi Biru sebagai Upaya Pemberdayaan Masyarkat di Desa Maukeli Kecamatan Mauponggo Kabupaten Nagekeo Nusa Tenggara Timur - Siska Novianti Siregar; Eusabius Separera Niron; Veronika Ruba Pena (Yayasan Literasi Sains Indonesia, 2026)
Maukeli Village in Mauponggo Subdistrict, Nagekeo Regency, possesses significant terrestrial and marine resources that have not been optimally managed. Limited public awareness of environmental management and sustainable resource utilization remains a major obstacle to improving community welfare. This Community Service Program (PKM) aimed to integrate the concepts of Green Economy and Blue Economy as a strategy for sustainable, locally based empowerment. The program was conducted from April to May 2025 and involved 10–15 community members using participatory methods, including counseling sessions, Focus Group Discussions (FGD), field observations, and pre- and post-activity evaluations through interviews and observation. The results indicate an increase in community knowledge regarding waste management and compost production derived from agricultural waste. Furthermore, a business group operating under the Blue Economy framework was established within the Village-Owned Enterprise (BUMDes). As a follow-up initiative, a preliminary seaweed cultivation plan based on coastal potential was formulated. The integration of Green and Blue Economy principles serves as a strategic foundation for enhancing ecological awareness, strengthening local institutions, and improving community welfare in Maukeli Village.